Far from shore - Thorpe, Kiki; Christy, Jana; Disney Enterprises (1996- ) (New York : Random House, 2015)
"The Never Girls have heard about a boy who lives in Never Land--a legendary boy who brings adventure wherever he goes. A boy named Peter Pan. Kate can't wait to meet him. But Tinker Bell knows that Peter is also good at causing trouble. Will this be an adventure, or a disaster?"--
"A Stepping Stone book."
520
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Characters in literature -- Juvenile fiction; Adventure and adventurers -- Juvenile fiction